Néstor Perlongher: The Intellectual Training Period (1968-1978) (Castilla. Estudios de Literatura, 2017)
The Argentine writer Néstor Perlongher’s work, developed throughout the years 1978-1992, has been frequently studied from its most notorious theoretical framework: the Post-Structuralism. However, there have been few attempts to understand the intellectual and cultural motives that led the author to assume and put into practice an anthropological work closely linked to this particular approach. Thus, this article aims to construct an appropriate sociocultural and political panorama that explains this theoretical drift as a result of his period of academic and activist training in Argentina during the years 1968-1978.
Keywords: Néstor Perlongher; Argentina; Postestructuralismo; intellectual traininig